Interaction of PUFAs and Doxorubicin: the Enhanced Toxicity in Breast Cancer Cells - Alicja Zajdel; Adam Wilczok (Polskie Towarzystwo Farmaceutyczne, 2023)
Doxorubicin (DOX) still remains one the most effective a clinical drug for breast cancer treatment. Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), the n-3 polyunsaturated fatty acids (PUFAs), exert pronounced toxicity against many types of cancers including breast cancer. That is why it was decided to investigate the mechanism of DOX and PUFAs toxicity on SK-BR-3 and MDA-MB-231 cells. The influence of DOX on the PUFAs oxidation and effect of DOX and EPA or DHA on cellular metabolic activity, viability, cytotoxicity, apoptosis and oxidative DNA damage in these cells were measured. DOX induced oxidation of the EPA and DHA. Toxicity of DOX and PUFAs towards breast cancer cells was associated with oxidative damage. These PUFAs reduced growth of the tested cells and caused their death. EPA and DHA potentiated DOX toxic effects through induction of oxidative DNA damage. The antitumor effect of PUFAs alone and combined with DOX strongly depended on induction of the oxidative stress that facilitated cell death. The observed changes of DOX toxicity induced by PUFAs suggest the possibility of their application in developing therapeutic anticancer strategies.